2023
DOI: 10.3389/fendo.2023.1195256
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal age on the birthweight of infants delivered from frozen-thawed blastocyst transfer cycles

Abstract: The aim of this study was to investigate whether maternal age had an effect on the birthweight of singletons delivered from frozen-thawed blastocyst transfer (FBT) cycles. A total of 1203 FBT cycles occurring between July 2011 and June 2021 at a single centre were retrospectively analysed. Based on the maternal age at FBT, the patients were divided into four groups: <30, 30–34, 35−37, and ≥38 years of age. Main outcomes measured included singleton birthweights, preterm births, large-for-gestational-age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Multivariate analysis also confirmed that the 35-37-year-old group was not associated with adverse pregnancy outcomes or obstetric or neonatal complications. This discovery is consistent with the conclusions of many scholars, such as Wang X and Ni Zhixin [ 24 , 25 ], who further confirmed the feasibility and safety of frozen-thawed high-quality SBT for women aged 35–37 years. Notably, multivariate regression analysis revealed that a maternal age between 38 and 40 years was associated with a 1.63-fold increased risk of adverse pregnancy outcomes but was not associated with obstetric or neonatal complications.…”
Section: Discussionsupporting
confidence: 90%
“…Multivariate analysis also confirmed that the 35-37-year-old group was not associated with adverse pregnancy outcomes or obstetric or neonatal complications. This discovery is consistent with the conclusions of many scholars, such as Wang X and Ni Zhixin [ 24 , 25 ], who further confirmed the feasibility and safety of frozen-thawed high-quality SBT for women aged 35–37 years. Notably, multivariate regression analysis revealed that a maternal age between 38 and 40 years was associated with a 1.63-fold increased risk of adverse pregnancy outcomes but was not associated with obstetric or neonatal complications.…”
Section: Discussionsupporting
confidence: 90%
“…Patients underwent endometrial preparation using two approaches ( 25 ). Natural cycles were recommended in women with regular ovulation and menstruation.…”
Section: Methodsmentioning
confidence: 99%
“…Endometrial preparation and luteal support protocols for FBT cycles at our center have been described in a previous article ( 26 ). In summary, two approaches to endometrial preparation exist.…”
Section: Methodsmentioning
confidence: 99%
“…With the patient's informed consent, all remaining embryos were cultured until D5 or D6 after fertilization. Upon formation of blastocysts, they were accessed in accordance with the Gardner scoring system (25). In brief, blastocysts were scored based on three aspects, i.e., blastocyst cavity expansion (1)(2)(3)(4)(5)(6), the quality of the inner cell mass (ICM) (A, B, C), and the quality of trophoblasts (TE) (A, B, C).…”
Section: Treatment Protocol and Embryo Evaluationmentioning
confidence: 99%